Immunomodulatory functions of Moringa oleifera (Lam.) - Adamu, Muhammad Umar; Lawal, Hamza; Ramasamy, Rajesh (Universiti Putra Malaysia, 2021)
Consumption of herbs as dietary supplements leads to beneficial effects on human health by maintaining a competent physiological system that balances homeostasis. It has been widely known that herbal-based products preserve good health by preventing or ameliorating chronic diseases such as metabolic, cardiovascular, inflammatory, neurodegenerative and neoplastic diseases. Although many herbs are known to boost the immune response via various mechanisms, only a few herbs are known traditionally to have a holistic beneficiary effect on the entire immune system, ranging from enhancing the stem cells pool to improving the quality of functional immune cells. In this review, significant scientific discoveries of Moringa oleifera’s immunomodulatory functions discussed in both in vitro and in vivo models. Besides its immunomodulatory actions, other reported biological functions of Moringa oleifera are also highlighted, along with relevant phytochemicals.